STUDI KINERJA PLATE HEAT EXCHANGER PADA SISTEM PENDINGIN PLTGU - Ridho Walikrom; Abdul Muin; Hermanto . (Jurnal Turbulen, 2018)
A plant (PLTGU) to operate with the maximum is to maintain the effectiveness of equipment used to keep clean of the pollutant factor. In a PLTGU, one of the cooling aids is a Plate Heat Exchanger (PHE) plate heat exchanger that uses water as a cooling fluid, the use of unclean water can decrease the effectiveness of the equipment due to the impurity factor. Here a study has been conducted to determine the effectiveness of the plate type heat exchanger before and after cleaning due to contamination by the cooling fluid. Data retrieval is done directly in the form of operational data directly and also through manual book.  Calculation of effectiveness is done by using the method of Number of Turbidity Unit (NTU). From the calculation of the effectiveness obtained before the cleansing of 83%, while after cleaning by 85%, here with the cleanup gives an increase of PHE effectiveness by 2%. Keywords: Efectivitnes, plate heat exchanger, NTU method